Solar-enhanced capture of aquatic uranium and organic pollutants with high efficiency using functionalized porous carbon nanotubes modified polysulfides - Lyu, Shiqi; Zainal Abidin, Zurina; Shean Yaw, Thomas Choong; Mukhtar Gunam Resul, Mohamad Faiz (Elsevier B.V., 2025)
Since solar assisted sorption strategy presented a promising prospect in the capture of aquatic pollutants, the design of an environmental-friendly and low-cost photothermal conversion sorbent would be highly sustainable. Herein, hydrophilic porous oxygen-modified polysulfide/multi-walled carbon nanotubes were prepared via the inverse vulcanization by integrating palm oil, sulfur, sodium chloride, sodium citrate and carbon nanotubes. By adjusting the filling content of carbon nanotubes, the evolution of microstructure, porosity, contact angle, photothermal effect, and mechanical property were systematically studied. Sorption behaviors of U(VI) under various hydrochemical conditions including contact time, solution pH, and initial U(VI) concentration were studied under simulated sunlight illumination and dark respectively. An enhancement of 28.6 %–90.2 % for maximum sorption capacity (208.7–335.1 mg/g) was achieved under sunlight comparing with that in dark. Beside a favorable recycling use, the practical sorption of U(VI) from natural seawater was evaluated. Moreover, hydrophobic polysulfide/multi-walled carbon nanotubes prepared without adding sodium citrate were applied to adsorb toluene and phenol under sunlight and dark. Sorption capacity improvements of 8.8 %–28.3 % for toluene and 9.6 %–28.5 % for phenol were presented under sunlight. This study provided new insights for the cost-effective and scalable capture of radionuclides and organic pollutant using solar-assisted polysulfide sorbents.